2008
DOI: 10.2220/biomedres.29.141
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-associated alteration in gene expression of importins and exportins in human leukemia HL-60 cells

Abstract: Employing the DNA microarray technique, we previously reported the alteration in gene expression of nucleocytoplasmic transport factors, importins and exportins, induced by 1,25-dihydroxyvitamin D3 (DVD) in human leukemia HL-60 cells. Here, we used the quantitative reverse transcription-polymerase chain reaction method to confirm such previous findings, and compared them with those from the cells treated with all-trans-retinoic acid (ATRA). The results indicated that the gene expression of the transport factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 12 publications
2
15
1
Order By: Relevance
“…When HL-60 cells were treated with 0.1 nM TPA for 1 day or 100 nM DVD for 3 days, a number of the cells became attached to the culture flask (data not shown). We reported that DVD suppressed cell growth (21) and that DVD and ATRA caused the change in gene expression of proteins involved in nucleocytoplasmic transportation (22). Thus, the present conditions appear to be sufficient to induce differentiation in HL-60 cells.…”
Section: Expression Of 67lrmentioning
confidence: 74%
See 2 more Smart Citations
“…When HL-60 cells were treated with 0.1 nM TPA for 1 day or 100 nM DVD for 3 days, a number of the cells became attached to the culture flask (data not shown). We reported that DVD suppressed cell growth (21) and that DVD and ATRA caused the change in gene expression of proteins involved in nucleocytoplasmic transportation (22). Thus, the present conditions appear to be sufficient to induce differentiation in HL-60 cells.…”
Section: Expression Of 67lrmentioning
confidence: 74%
“…To prevent possible contamination, samples were treated with deoxyribonuclease (RT-grade, Wako Pure Chemical Industries Ltd.) as recommended by the manufacturer. Q-PCR was performed using the Thermal Cycler Dice (TaKaRa Bio., Tokyo, Japan) as described previously (22). Primers for 67LR designed using a software OLIGO4.0-s were 5'-GC CATTGAAAACCCTGCTG-3' and 5'-GCTGCCTG GATCTGGTTAGTG-3' (GenBank accession no.…”
Section: Quantitative Reverse Transcription Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining portions of the liver samples were kept at −85°C in RNAlater (Applied Biosystems Japan Ltd., Tokyo, Japan) for Q-PCR. Q-PCR was performed using the Thermal Cycler Dice (TaKaRa Bio., Tokyo, Japan) as described previously (19). Primers were purchased from TaKaRa Bio., and are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…To prevent possible contamination, samples were treated with deoxyribonuclease (RT-grade, Wako Pure Chemical Industries Ltd.) as recommended by the manufacturer (1). Q-PCR was performed using the Thermal Cycler Dice (TaKaRa Bio., Tokyo, Japan) as described previously (1,15). Primers were purchased from TaKaRa Bio.…”
Section: Q-pcrmentioning
confidence: 99%